REPRESENTASI REVOLUSI INDONESIA DALAM PUISI â€œRAPAT MENGGANYANG 7 SETANâ€ KARYA H.R. BANDAHARO - Artika, I Wayan (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
The present study aimed to examine the representation of Indonesian revolution in the poetry â€œRapat Mengganyang 7 Setanâ€ written by H. R. Bandaharo. The meanings of the poetry are uncovered by investigating the mutual relationship between the poetry and the work and speech of President Soekarno as well as the written work of D.N. Aidit. The study used a qualitative research design, and the data were analyzed by using parallel reading method. The study results showed that the representation of Indonesian revolution is realized through the theme and diction of the poetry which are derived from sayings/slogans during the revolution time. The mutual relationship between the poetry â€œRapat Mengganyang 7 Setanâ€ and President Soekarnoâ€™s speech and D.N. Aiditâ€™s written work are based on Mukadimah Lekra (Lekra Preamble), Communityâ€™s Culture Conception, and method of combination principle 1-5-1. The representation of Indonesian revolution in the poetry shows literature as part of political movement to reach the goal of Indonesian revolution, that is, just and prosperous community.Key words: representation, Indonesian revolusion, new historicism